Part 1: The influence of personal and situational predictors on nurses' aspirations to management roles: preliminary findings of a national survey of Canadian nurses. (25th October 2012) - Spence Laschinger, Heather K.; Wong, Carol A.; Macdonald‐Rencz, Sandra; Burkoski, Vanessa; Cummings, Greta; D'amour, Danielle; Grinspun, Doris; Gurnham, Mary‐Ellen; Huckstep, Sherri; Leiter, Michael; Perkin, Karen; Macphee, Maura; et al.
<x xml:space="preserve">Abstract</x> Aim To examine the influence of personal and situational factors on direct‐care nurses' interests in pursuing nursing management roles. Background Nursing managers are ageing and nurses do not appear to be interested in nursing management roles, raising concerns about a nursing leadership shortage in the next decade. Little research has focused on factors influencing nurses' career aspirations to nursing management roles. Methods A national survey of nurses from nine Canadian provinces was conducted (n = 1241). Multiple regression was used to test a model of personal and situational predictors of nurses' career aspirations to management roles. Results Twenty‐four per cent of nurses expressed interest in pursuing nursing management roles. Personal and situational factors explained 60.2% of nurses' aspirations to management roles. Age, educational preparation, feasibility of further education, leadership self‐efficacy, career motivation, and opportunity to motivate others were the strongest predictors of aspirations for management roles. Conclusions Personal factors were more strongly associated with career aspirations than situational factors. There is a steady decline in interest in management roles with increasing age. Implications for nursing management Nursing leadership training to develop leadership self‐efficacy (particularly for younger nurses) and organizational support for pursuing advanced education may encourage nurses to pursue nursing management roles.